Effect of Murraya Koenigii and Aegle Marmelos in Management of Bovine Anoestrus Under Field Conditions - Chaudhari, Chandrakant Fuljubhai; Sutaria, Tarunkumar Virabhai; Chaudhari, Ravjibhai Karshanbhai; Nakhashi, Hareshbhai Chhotalal; Suthar, Babulal Natvarlal; Patel, Mayank Pravinbhai; Chaudhary, Bharatkumar Govindbhai (The Indian Journal of Animal Reproduction, 2025)
Total 33 bovines with the history of not exhibiting the signs of estrous were screened by per rectal examination to rule out the anoestrus condition and included in the present study. The selected animals were divided into three groups. Animals in Group 1 (n=14) were supplemented with grinded dried leaf powder of Murraya koenigii @ 210mg/kg and Aegle marmelos @ 270 mg/kg for 9 days orally; Group 2 (n=12) were supplemented with commercially available oral herbal estrus inducer and Group 3 (n=07) were kept as control. All the animals were monitored for expression of estrus and the animals not exhibited estrus within 30 days of the treatment were considered as not responding to the treatment. Responded animals were bred by artificial insemination and observed for estrus induction response, estrus induction interval and conception rate at induced estrus. Estrus induction response was significantly (p